O interessado dá um jeito: a relação entre ambição política e alocação de emendas individuais no Brasil - Lima, Albany Ferreira (2018)
What is the effect of the allocation of individual amendments on the political ambition of Brazilian Federal Deputies? In order to answer this question, this dissertation tries to estimate the effect of the allocation of individual amendments on the political ambition of Brazilian parliamentarians. The investigation took place on the 54th Legislature (2011 and 2015) of the Chamber of Deputies, and covers data on individual amendments, the result of the vote of the deputies, and their experience in the Chamber of Deputies and in elective positions in the Executive. Methodologically, descriptive and multivariate statistics were used to test the hypothesis that the concentration of individual amendments has a positive effect on the choice of political ambition. The results show that the correlation is positive, however, the low statistical significance of the model led to the rejection of the main hypothesis. This dissertation contributes to the test of hypotheses in the literature about the career choice of parliamentarians, and their allocation of individual amendments.